Potential assessment and tactics of increasing electric energy efficiency of underground iron-ore mining enterprises - Синчук, Олег Николаевич; Синчук, Игорь Олегович; Семёнович, Эдуард Гузов; Яловая, Алёна Николаевна; Баулина, Марина Анатольевна (Technology audit and production reserves, 2014)
The paper contains the analysis of energy consumption volumes at iron-ore enterprises with the underground mining method. It is shown that the share of electric energy accounts for about 90 % of the total energy consumption. The amount of energy consumed for technological purposes, as well as its production cost has been increasing every year. Herewith, it is necessary to consider the fact that production cost variations of the produced iron ore have no obvious correlation. The ways of increasing the electric energy efficiency at mining enterprises are considered. Specific recommendations for improving the energy efficiency of the domestic underground iron-ore production are given. First of all, it is proposed assessing current potentials of specific production types that will allow optimizing the process of energy consumption by certain types of consumers. Special attention is paid to considering the peculiarities of mining enterprises. An integrated solution to improving the energy efficiency of domestic iron-ore enterprises also requires organizational measures, beginning with the introduction of an effective energy management system.